2020
DOI: 10.3892/ijmm.2020.4468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eleutheroside B1 on non‑coding RNAs and protein profiles of influenza A virus‑infected A549 cells

Abstract: Influenza viruses often pose a serious threat to animals and human health. In an attempt to explore the potential of herbal medicine as a treatment for influenza virus infection, eleutheroside B1, a coumarin compound extracted from herba sarcandrae, was identified, which exhibited antiviral and anti-inflammatory activities against influenza A virus. In this study, high-throughput RNA sequencing and isobaric tags for relative and absolute quantification (iTRAQ) assays were performed to determine alterations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
2
2
0
Order By: Relevance
“…Furthermore, they agree with preclinical in vitro and in vivo studies of Andrographis paniculata and Eleutherococcus senticosus preparations [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Antiviral activity of Eleutherococcus extracts were demonstrated in experimental model systems in which rodents were infected with H1N1 influenza A virus [23][24][25][26], human rhinovirus and respiratory syncytial virus [24]. The antiviral effect of Andrographis extracts [27] were demonstrated against H1N1 influenza A [28-30], H5N1 avian influenza [31], Chikungunya [32] Dengue [33,34], and SARS-CoV-2 [35][36][37][38] viruses.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, they agree with preclinical in vitro and in vivo studies of Andrographis paniculata and Eleutherococcus senticosus preparations [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Antiviral activity of Eleutherococcus extracts were demonstrated in experimental model systems in which rodents were infected with H1N1 influenza A virus [23][24][25][26], human rhinovirus and respiratory syncytial virus [24]. The antiviral effect of Andrographis extracts [27] were demonstrated against H1N1 influenza A [28-30], H5N1 avian influenza [31], Chikungunya [32] Dengue [33,34], and SARS-CoV-2 [35][36][37][38] viruses.…”
Section: Introductionsupporting
confidence: 81%
“…These results are in line with the results of a prospective, multicenter, open-label, and randomized controlled trial of Xiyanping intravenous injection (iso-andrographolide-19sodium sulfate, a synthetic derivative of andrographolide, the primary anti-inflammatory compound of Herbal Andrographidis) in patients with mild to moderate COVID-19, where significant reduction in the time to cough relief, fever resolution and virus clearance were demonstrated [17]. Furthermore, they agree with preclinical in vitro and in vivo studies of Andrographis paniculata and Eleutherococcus senticosus preparations [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Antiviral activity of Eleutherococcus extracts were demonstrated in experimental model systems in which rodents were infected with H1N1 influenza A virus [23][24][25][26], human rhinovirus and respiratory syncytial virus [24].…”
Section: Introductionsupporting
confidence: 62%
“…This combination was tested in controlled clinical trials for the treatment of common cold and influenza‐associated uncomplicated upper respiratory infections as well as for the prevention of common colds 421–424 . The studies confirmed the safety and superior efficacy of this combination regimen as compared with monodrug therapy, 425 presumably because of its antiviral effects, 426–432 effects on innate and adaptive immunity, 433–437 and anti‐inflammatory, antioxidant, and detoxifying effects 438–441 of both adaptogenic plants as well as due to their synery 25 . It should be noted that the postmarketing pharmacovigilance assessment of Kan Jang showed a high benefit–risk ratio: one adverse event in about 100,000 patients was recorded for the 23‐year period from the adverse event reports (concerning mainly allergic reactions) to the Swedish and Danish medical product agencies.…”
Section: Current and Prospective Use Of Adaptogens In Stress‐induced And Aging‐related Diseasesmentioning
confidence: 84%
“…L antigen family member 3 (LAGE3, NM_006014), a member of the LAGE gene family, is ubiquitously expressed in somatic tissues in humans [9]. LAGE3 is also considered a component of the kinase, endopeptidase and other proteins of small size/endopeptidase-like kinase chromatin-associated protein complex, playing a vital role in the regulation of the positive transcription mediated by RNA polymerase II, tRNA metabolic processing and ncRNA processing [10,11]. The mutation of LAGE3 is linked with nephrotic syndrome associated with primary microcephaly, brain abnormalities and growth retardation [12].…”
Section: Introductionmentioning
confidence: 99%